Kedudukan Pihak Tergugat dan Turut Tergugat dalam Perkara Perdata Ditinjau dari Akibat Hukumnya (Analisis atas Putusan Pengadilan Negeri Nomor 7/Pdt.G/2020/PN. Sbr Sumber) - Dompas, Pascall Dimitri; Tobing, Padimun Lumban (PT Elaborium Elevasi Indonesia, 2025)
In civil procedural law, the position of the Defendant and Co-Defendant plays an important role in determining the direction and outcome of the trial. The Defendant is the main party sued by the Plaintiff for violation of rights or obligations, while the Co-Defendant is a party who is not directly involved in the main dispute, but whose existence is considered important to resolve the case as a whole, especially in order to fulfill the formalities of the lawsuit regarding the completeness of the parties being sued. Formulation of the Problem in this study: 1. How to determine the position of the Parties as Defendants and Co-Defendants in a Civil Lawsuit and what are the legal consequences? 2) Are the Legal Considerations of the Panel of Judges in the Decision of the Sumber District Court Number 7 / Pdt.G / 2020 / PN. Sbr Sumber District Court, in accordance with the provisions and principles of Civil Procedure Law? The research method used is a normative legal research method where data is obtained from legal materials sourced from literature in the form of books, regulations and court decisions. Research shows that a person is placed as a Defendant and as a Co-Defendant is determined based on the role of a person in an act that causes harm to the Plaintiff. A person whose actions cause harm to the Plaintiff, then the person who causes the harm is placed as a Defendant. Meanwhile, a Co-Defendant is a person who due to a situation or status has a role so that the Defendant can carry out his actions, so that the Co-Defendant cannot be sentenced to a condemnatory or punitive sentence. The legal considerations of the Judge in the Decision of the Sumber District Court Number 7/Pdt.G/2020/PN. Sbr which sentenced the Co-Defendant to share the losses and even confiscated his property, in addition to being contrary to civil procedural law regarding the status of the Co-Defendant, the verdict also contradicts the principle of ultra petita civil law, namely the principle where the judge may not grant more than what the Plaintiff requested. In this decision, the Judge has given more than the Plaintiff's petitum, namely Sentencing the Co-Defendant to be jointly and severally liable to pay compensation and confiscate the Defendant's property.